The Effect of Digitalization on Advancing Psychology for Sustainable Development at Imo State University - Okpara, Chizoma Catherine; Agwu, Christopher Okechikwu (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
Digitization has greatly impacted the field of psychology, providing new tools and methods for research and analysis. Using digital technology, psychologists can collect accurately. This led to progress in the understanding of human behaviour and opened up new possibilities for sustainable development in education. This study investigated the effect of digitization on advancing psychology for sustainable development at Imo State University Owerri. The study was guided by two research questions and two hypotheses. The study adopted a quasi-experimental research design. The population included 729 lecturers (531 male and 198 female) at Imo State University. The sample for this study consisted of 200 (100 male and 100 female) educators from Imo State University using a stratified random sampling technique. The researcher developed and utilized the Psychology Advanced Test (PAT) for data collection, validated using measurement and evaluation experts. A reliability coefficient of 0.87 was obtained for the PAT using the Kuder-Richarson 21 method. Research questions were answered using mean and standard deviation, while hypotheses were tested using a t-test and two-way ANOVA at a 0.05 level of significance. The findings revealed that there was a significant difference between the mean scores of educators exposed to mHealth and educators exposed to traditional personal therapies in psychology for sustainable development. Gender was also found to be significant in average exposure to mobile health (mHealth). The study recommended that higher institutions support researchers around the world who help monitor the effectiveness of interventions aimed at promoting sustainable behaviour.